Efforts to Improve Clean and Healthy Living Behaviors in Elementary School Level Students Through The Essence of The Small Doctor Program in The School Environment - Vina Oktiarina (Literasi: Jurnal Ilmu Pendidikan, 2023)
This study aims to 1) determine the relationship between small doctor programs and clean and healthy living behaviors in elementary school students; 2) knowing the relationship between the school environment and clean and healthy living behaviors in elementary school students. This research was conducted at an elementary school in Tembong Village, Cipocok Jaya District, Serang City with a total sample taken of 78 simple random sampling students. Data analysis using correlation coefficient analysis with the SPSS program. The results of this study show that there is a positive and significant relationship between small doctor programs and clean and healthy living behaviors. There is a positive and significant relationship between the school environment and clean and healthy living behaviors